Formación de hidroxiapatita sobre una superficie polimérica por un método biomimético - Martínez-Pérez, C. A.; Martínez-Villafañe, A.; Romero-García, J. (Revista Mexicana de Ingenieria Biomedica, 2001)
Biomimetic growth of calcium phosphate compound on porous polyurethane (PU) treated with tetraethyl orto-silicate (TEOS) and soaked in simulated body fluid solution was studied using scanning electron microscopy (SEM), energy dispersive X-ray analysis, and Fourier Transformed infrared spectroscopy-attenuated total reflectance (FTIR-ATR). Polyurethane was treated with TEOS in order to lead to the formation of silanols groups which stimulated the growth of hydroxyapatite when immersed in simulated body fluid solution (SBF). Polyurethanes not treated with TEOS did not how calcium phosphate growth upon immersion in SBF solution. The Ca and P determined by EDAX and inductively coupled plasma spectroscopy (ICP) analysis revealed that surface layer was no – stoichiometric hydroxyapatite, but carbonated– containing hydroxyapatite with Ca/P ratio of 1.5 – 1.6, this was confirmed with FTIR-ATR.